The Artificial Intelligence Revolution In University Language Teaching: Applications And Futures] - Fatima Zohra Sehlaoui (The Journal of Studies in Language, Culture and Society, 2025)
The advent of artificial intelligence (AI) is currently precipitating a global revolution in technology, with profound implications for scientific research and numerous facets of contemporary life. Among its promising applications, the integration of AI into education and learning stands out, particularly in light of recent recommendations by the French Ministry of Higher Education and Scientific Research to enhance proficiency in the English language. This priority is reflected in the incorporation of English into degree requirements and the increasing adoption of English-language instruction in universities. This article examines the convergence of AI technologies with language learning and teaching, emphasizing prominent applications such as Speak, Ewa, Grammarly, Duolingo, Getpronounce, and HelloTalk. For instance, Duolingo employs a pedagogical strategy that incorporates a variety of techniques, including listening to word pronunciation, reading sentences, audio recordings, sentence construction through word arrangement, and image-word association. This approach is especially pertinent in light of ministerial recommendations on English, which have now been incorporated into final assessments and initial teaching in universities. Furthermore, the article investigates the potential for optimizing the utilization of these AI applications for language learning among university students. To this end, a questionnaire has been developed for language students (English and French) to ascertain their perspectives on the subject matter. The objective is to investigate the potential of these tools to facilitate the development of language proficiency, fulfill academic expectations, and promote the integration of foreign languages in higher education. L’avènement de l’intelligence artificielle (IA) est actuellement précipitant une révolution technologique mondiale, avec des implications profondes pour la recherche scientifique et de nombreuses facettes de la vie contemporaine. Parmi ses applications prometteuses, l’intégration de l’IA dans l’éducation et l’apprentissage se distingue, Cette initiative est particulièrement importante à la lumière des récentes recommandations du ministère français de l’enseignement supérieur et de la recherche scientifique visant à améliorer les compétences en anglais. Cette priorité se reflète dans l’intégration de l’anglais aux exigences des diplômes et dans l’adoption croissante de l’enseignement en langue anglaise dans les universités. Cet article examine la convergence des technologies d’IA avec l’apprentissage et l’enseignement des langues, en mettant l’accent sur les applications importantes telles que Speak, Ewa, Grammarly, Duolingo, Getpronounce et HelloTalk. Par exemple, Duolingo utilise une stratégie pédagogique qui intègre une variété de techniques, y compris l’écoute de la prononciation des mots, la lecture de phrases, les enregistrements audio, Construction de la phrase par arrangement de mots et association image-mot. Cette approche est particulièrement pertinente à la lumière des recommandations ministérielles sur l’anglais, qui ont maintenant été intégrées dans les évaluations finales et l’enseignement initial dans les universités. En outre, l’article étudie le potentiel d’optimisation de l’utilisation de ces applications IA pour l’apprentissage des langues chez les étudiants. À cette fin, un questionnaire a été élaboré pour les étudiants en langues (anglais et français) afin de connaître leurs points de vue sur le sujet. L’objectif est d’étudier le potentiel de ces outils pour faciliter le développement des compétences linguistiques, répondre aux attentes académiques, Promouvoir l’intégration des langues étrangères dans l’enseignement supérieur.